2009
DOI: 10.3109/10641960903407058
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Self-Monitoring of Urinary Salt Excretion in Hypertensive Patients

Abstract: We investigated the usefulness of measuring urinary salt excretion by using a self-monitoring device. Subjects were 34 hypertensive patients who underwent successful 24-h home urine collection five times and 25 volunteers. Four volunteers were diagnosed as having hypertension based on home blood pressure (BP) readings. All subjects were asked to measure daily urinary salt excretion for 30 days by using a self-monitoring device which estimates 24-h salt excretion by overnight urine. The mean urinary salt excret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
4
11
0
Order By: Relevance
“…In the current study, we used early morning spot urine samples to estimate daily salt intake. Previous reports have shown that the urine sodium‐to‐creatinine ratio determined from early morning spot urine samples correlated well with urinary sodium excretion values calculated over a 24‐hour period . Our own results confirmed that estimates of daily salt intake based on the spot urine samples were highly reproducible, with little variation observed from day to day for each individual (Table ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the current study, we used early morning spot urine samples to estimate daily salt intake. Previous reports have shown that the urine sodium‐to‐creatinine ratio determined from early morning spot urine samples correlated well with urinary sodium excretion values calculated over a 24‐hour period . Our own results confirmed that estimates of daily salt intake based on the spot urine samples were highly reproducible, with little variation observed from day to day for each individual (Table ).…”
Section: Discussionsupporting
confidence: 87%
“…Previous reports have shown that the urine sodium-to-creatinine ratio determined from early morning spot urine samples correlated well with urinary sodium excretion values calculated over a 24-hour period. [13][14][15][16][17] Our own results confirmed that estimates of daily salt intake based on the spot urine samples were highly reproducible, with little variation observed from day to day for each individual (Table 1). Using this method, we found that excessive salt intake reduced the efficacy of ddavp treatment in Japanese patients with nocturnal enuresis.…”
Section: Discussionsupporting
confidence: 71%
“…Ohta et al reported that urinary salt excretion is reduced by the use of a self-monitoring device by hypertensive patients, and that BW is significantly correlated with salt excretion (14). Meland et al also reported that during a randomized controlled trial for 12 weeks, BP decreased significantly in hypertensive patients who were using self-monitoring of urine for Cl -in addition to receiving nutritional instruction (15).…”
Section: Discussionmentioning
confidence: 89%
“…Ohta et al also reported that salt excretion measured with a self-monitoring device correlated well with that determined by 24-h home urine evaluation in hypertensive subjects (r=0.63, P<0.01) (14). Since the self-monitoring device can be used at home to evaluate daily urinary salt excretion, it can be used as a strong motivational tool to help individuals reduce salt intake.…”
Section: Discussionmentioning
confidence: 90%
“…13 The mean salt excretion for 30 days was 8.4 ± 1.5 g per day, and the range (maximum-minimum value) was 5.5 ± 2.1 g per day.…”
Section: Discussionmentioning
confidence: 99%